Poesia negra brasileira: o desmantelar das grilhetas da Sciencia do Século XIX - Souza, Alan Fernandes de (2009)
The present study focuses the representation of racial relations in Brazilian Black poetry. Thus, we elected as our research object samples of the poetic production of two different moments: the first, implying the period generally referred to as Brazilian Modernism. The second, the poetic production of the 1950ies until contemporary times which, we call Late Modernism. Such poetic productions were selected as our corpus with the intention to indicate, by the analysis of the simbology and allegories implicit, the mimetic representation of different forms through which stereotypes and prejudices come into form, a racism deeply rooted in the collective imaginary of Brazilian society, having as its basis the racial theories of the 19th Century. Thus, we revise the history of Brazilian racial myths, the ideological and cultural basis on which those myths are founded, the historiography of Brazilian Black poetry, the process of elaboration of the mimesis and the literary project that such poetry implemented in the country. Our decision to deal with Brazilian Black poetry as our corpus is basically connected to our passion to poetry in general, and to Black poetry, in particular; we also decided for this focus based on our political and social option to struggle against racism and its expressions. We also believe we can interrogate discussions and perspectives on Black poetry we disagree with, despite their frequent presence in academic debates; we understand this as an opportunity to analyze the tensions in the academic institutional sphere in a broader sense. Besides, our research tries to deconstruct the idea that texts permeated by revolt or denounce of racism cannot have literary quality. On the contrary, the political tone of Black poetry, as we see it, is part of its structure, of its theme. Some critics defend that the political tone of Black poetry is responsible for the reduced number of its readers. We believe this statement has to be revised and reexamined in the specific context of Brazil. In this sense, we analyze literary texts making use of interdisciplinary theoretical and methodological support, which allows us to develop a reading that points to the existing relation between literary text and the socio-cultural context in which it is inserted. So, we articulate the poetic text with other discourses of social sciences, especially with the historical and sociological discourses, without forgetting that our attention should concentrate on the analyzed poetry. We also intend to follow the critical attitude defended by Antonio Candido (1985), when he states that social factors should be observed as elements which assume the role of structuring the piece of work. So, poetry and society present themselves as inseparable elements of our study, which propose to free Brazilian Black poetry of reductionist or de-contextualized readings, responsible for the maintenance of racism in the literary canon and in its critics.